ANALYSIS OF THE READINESS OF SECONDARY SCHOOL TEACHERS REGARDING THE DIFFERENTIATED LEARNING SYSTEM IN THE INDEPENDENT CURRICULUM IN ENTREPRENEURSHIP SUBJECTS - Fadilla Yessa; Yelnita Yelnita; Monica Ihsan Almauiza; Susi Evanita; Friyatmi Friyatmi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2023)
The study aims to analyze the readiness of secondary school teachers in terms of contents, process, products, learning environment and identify the challenges teachers face regarding differentiated learning in the independent curriculum in entrepreneurship—the method used in this study quantitative research. Data were collected through questionnaires to 30 teachers in three secondary schools in West Sumatra. This research focuses on entrepreneurship teachers at MAN Insan Cendekia Padang Pariaman, SMK N 2 Pariaman City, and MAN 1 Bukittinggi regarding the differentiated learning system in the independent curriculum—the technique of collecting data using questionnaires reinforced by observation and interviews. The data analysis technique uses descriptive statistics by calculating the mean for each item and the overall score of the questionnaire. This study found that secondary school teachers' readiness for differentiated learning in content, process, product, and learning environment is good. Where differentiation in content is 4.44, teachers have used small groups to teach skills students, differentiation in the process is 3.82, teachers give students Flexibility in the results of the homework assigned, differentiation in products is 4.28, teachers have designed learning in favour of students. Differentiation in the learning environment is 4.27; teachers have helped students understand that some students need to move to learn while others prefer to sit quietly. As well as the challenges teachers face regarding differentiated learning in the independent curriculum in entrepreneurship subjects have not been maximized, but in reality, in the classroom, it is still found that teachers have difficulty managing the class.